PARTISIPASI POLITIK DAN KETERWAKILAN PEREMPUAN DI PARLEMEN - Amareta Kristina Kesumadewi; Dian Iskandar (Jurusan Ilmu Pemerintahan, 2022)
This article aims to elaborate on women’s politicalparticipation and representation in parliament in Indonesia.To answer how women's political participation andrepresentation in parliament, the researcher use qualitativeresearch methods with data collection techniques is aliterature study, while analysis uses qualitative analysisTheresults found are that women's affirmations in parliamenthave not yet reached 30 percent, and the quantity is stillvolatile from the previous three election periods so women'sparticipation in parliament faces obstacles that it has animpact on gender-biased policy making because of a stronglypatriarchal culture, so that issues women's issues in allaspects are not accommodated. Therefore there is a need forimprovements in several areas such as institutional andprocedural changes, representation, and outcomes as well asdiscourse on women in parliament.